Amelia Earhart flying solo - Burke, John 1915-1975.; Burke, John 1915-1975. (New York, NY Sterling, 2007)
A biography of one of America's most famous pilots, who mysteriously disappeared in 1937 while trying to fly around the world.
"A Flying Point Press book"--T.p. verso.
Abridged ed. of: Winged legend : the story of Amelia Earhart. Putnam, c1970.
Maps on endpapers.
UCWS-2015-G-2473 donated by Adrienne Maguddayao
Keywords: Earhart, Amelia -- 1897-1937.; Earhart, Amelia -- 1897-1937.; Women air pilots -- United States -- Biography; Air pilots -- United States -- Biography; Air pilots; Women -- Biography